Effect of pedalling rates on physiological response during endurance cycling - Lepers, R.; Millet, G. Y.; Maffiuletti, N. A.; Hausswirth, C.; Brisswalter, J. (European Journal of Applied Physiology, 2001)
This study was undertaken to examine the effect of different pedalling cadences upon various physiological responses during endurance cycling exercise. Eight well-trained triathletes cycled three times for 30 min each at an intensity corresponding to 80% of their maximal aerobic power output. The first test was performed at a freely chosen cadence (FCC); two others at FCC-20% and FCC+20%, which corresponded approximately to the range of cadences habitually used by road racing cyclists. The mean (SD) FCC, FCC-20% and FCC+20% were equal to 86 (4), 69 (3) and 103 (5) rpm respectively. Heart rate (HR), oxygen uptake (VO2), minute ventilation (VE) and respiratory exchange ratio (R) were analysed during three periods: between the 4th and 5th, 14th and 15th, and 29th and 30th min. A significant effect of time (P<0.01) was found at the three cadences for HR, VO2 . The VE and R were significantly (P<0.05) greater at FCC+20% compared to FCC-20% at the 5th and 15th min but not at the 30th min. Nevertheless, no significant effect of cadence was observed in HR and VO2 . These results suggest that, during high intensity exercise such as that encountered during a time-trial race, well-trained triathletes can easily adapt to the changes in cadence allowed by the classical ear ratios used in practice.